Sex differences in burnout and work-family conflict among Chinese emergency nurses: a cross-sectional study - Diao, Dongmei; Chen, Xiaoli; Zhong, Luying; Zhang, Hao; Zhang, Jianna (Frontiers in Public Health, 2024)
IntroductionWork–family conflict and burnout have become pressing concerns in nursing profession. These factors negatively affect nurses' health and work performance and therefore negatively influence the quality and safety of patient care. Whereas, nursing is a female-dominated profession. Studies have found that male nurses have higher level of depersonalization dimension of burnout than female nurses. Female nurses present higher level of emotional exhaustion dimension of burnout than male nurse. This study aimed to apply sex-specific analyses to investigate the associations between dimensions of burnout and work–family role behavior conflict among Chinese emergency department nurses.MethodsThis was a cross-sectional research. A questionnaire comprising items on demographic characteristics, work–family role behavior conflict, and burnout information, was distributed among emergency department nurses from 30 tertiary hospitals across mainland China, between December 26, 2023, and January 18, 2024.ResultsThis study's sample comprised 1,540 nurses. The total work–family role behavior conflict scores were 42.23 and 43.4, and the total burnout scores were 11.14 and 11.63 for female and male nurses, respectively. Significant differences were observed in comparisions of age, marital status, fertility status, education level, job title, work experience, night shift frequency, smoking status, and drinking status by sex. Correlation analyses revealed that burnout and work–family role behavior conflicts were positively associated with both sexes. Multiple linear regression analyses indicated that three dimensions of burnout including emotional exhaustion, depersonalization, and reduced work accomplishment significantly affected work–family role behavior conflict in both sexes. Compared with emotional exhaustion and reduced work accomplishment dimensions, depersonalization dimension of burnout affected work–family role behavior conflicts the most in male emergency nurses. Emotional exhaustion and depersonalization dimensions of burnout explained more of the variance in work–family role behavior conflict compared with redeuced work accomplishment dimension for female emergency nurses.ConclusionReducing depersonalization among emergency department male nurses and emotional exhaustion and depersonalization for female emergency department nurses, are crucial for decreasing work–family role behavior conflicts. Future studies should explore differences in burnout level among male and female nurses for a long time.